Base temperature for leaf appearance and phyllochron of selected strawberry cultivars in a subtropical environment - Rosa,Hamilton Telles (2011)
Leaf development is characterized by the appearance of new leaves and is related to crop leaf area index, which affects the interception of solar radiation used for photosynthesis and biomass production and ultimately defines crop yield. The objectives of this paper were to estimate the base temperature for leaf appearance and to determine the phyllochron of two strawberry cultivars considering several planting dates. A two-year field experiment was conducted during 2008 and 2009 in Santa Maria (RS). The cultivars Arazá (early) and Yvapitá (late) were used at three planting dates in both years. Base temperature (Tb) was estimated using the Mean Square Error (MSE) approach of the regression between accumulated leaf number (LN) and accumulated thermal time (ATT). The phyllochron was calculated as the inverse of the slope of the regression of LN against ATT. Estimated Tb for leaf appearance in both cultivars was 0 °C. Variations in phyllochron were observed among the two cultivars, among planting dates and also during the plant developmental period of each cultivar. Before flowering, the phyllochron was similar in both cultivars and after flowering it was higher in cultivar Arazá. Phyllochron was greater for later planting dates and increased at short photoperiods in Fall and Winter. Results showed that both cultivars have a typical long-day plant response because phyllochron decreased as photoperiod increased up to approximately 11.8 hours, and phyllochron was the lowest at longer photoperiod.